2019
DOI: 10.3847/1538-4357/ab4c32
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Destruction in a Low-mass Galaxy Environment: The Discovery of Tidal Tails around DDO 44*

Abstract: We report the discovery of a 1 • (∼ 50 kpc) long stellar tidal stream emanating from the dwarf galaxy DDO 44, a likely satellite of Local Volume galaxy NGC 2403 located ∼ 70 kpc in projection from its companion. NGC 2403 is a roughly Large Magellanic Cloud stellar-mass galaxy 3 Mpc away, residing at the outer limits of the M 81 group. We are mapping a large region around NGC 2403 as part of our MADCASH (Magellanic Analogs' Dwarf Companions and Stellar Halos) survey, reaching point source depths (90% completene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 145 publications
0
30
0
Order By: Relevance
“…The ΛCDM theory of a hierarchical universe predicts the presence of very lowmass halos interacting with dwarf galaxies in low-density environments (e.g., Guo et al 2011;Sales et al 2013). Some examples of these interactions were recently discovered by the MADCASH Survey (Carlin et al 2016(Carlin et al , 2019. In this context, we propose that an alternative scenario is that a small galactic system interacted with the star-forming companion generating the observed blue stream, and that later both of them fell simultaneously towards the NGC 7241.…”
Section: The Origin Of Blue Streams: Insights From Theory Simulations...mentioning
confidence: 80%
“…The ΛCDM theory of a hierarchical universe predicts the presence of very lowmass halos interacting with dwarf galaxies in low-density environments (e.g., Guo et al 2011;Sales et al 2013). Some examples of these interactions were recently discovered by the MADCASH Survey (Carlin et al 2016(Carlin et al , 2019. In this context, we propose that an alternative scenario is that a small galactic system interacted with the star-forming companion generating the observed blue stream, and that later both of them fell simultaneously towards the NGC 7241.…”
Section: The Origin Of Blue Streams: Insights From Theory Simulations...mentioning
confidence: 80%
“…We evaluate fh ( x) on an 800 2 grid over the full field of view and use kernel bandwidths of 200, 300, 500, and 1000 pc at the assumed distances of our hosts to produce four maps that resemble the RGB maps common in other studies (e.g., Carlin et al 2019). An example of a KDE map with h = 300 pc for NGC 4395 is shown in Figure 2.…”
Section: Dwarf Search Methodsmentioning
confidence: 99%
“…Using these LBT data, Garling et al (2020) showed that the Fornax-analog DDO 113, which ceased forming stars less than 1 Gyr ago (Weisz et al 2011), is undisrupted and was likely quenched due to the cessation of cold gas inflows upon entering the halo of its host, the LMC-analog NGC 4214. Similarly, Carlin et al (2019) showed that DDO 44, a dwarf satellite of similar luminosity that also quenched about a Gyr ago (Karachentsev & Kaisin 2007;Weisz et al 2011), was also tidally disrupted by its ∼ 2×LMC-mass host, NGC 2403. These results are somewhat surprising when compared to the SAGA survey, which focuses on MW-mass hosts and has found predominantly star-forming dwarf satellite galaxies (Geha et al 2017;Mao et al 2020).…”
Section: Introductionmentioning
confidence: 92%
“…It has a satellite galaxy DDO 44 (M 𝑉 = -12.5), and recently a smaller dwarf, called MADCASH-1 (M 𝑉 = -7.7), was discovered by (Carlin et al 2016). Although DDO 44 shows signs of interacting Carlin et al (2019), NGC 2403 itself reveals a remarkably undisturbed HI disk (de Blok et al 2008;Williams et al 2013). This, and its relative isolation, suggests it is a galaxy that has not undergone a strong tidal interaction nor experienced ram pressure stripping.…”
Section: Introductionmentioning
confidence: 99%